Aesthetical and Accuracy Outcomes of Reconstruction of Maxillary Defect by 3D Virtual Surgical Planning - Wang, Yang; Qu, Xingzhou; Jiang, Junjian; Sun, Jian; Zhang, Chenping; He, Yue (Frontiers in Oncology, 2021)
Background: Reconstruction of maxillary defect resulting from trauma or oncology surgery is of great importance for patients with physical and psychological complications. The virtual surgical planning (VSP) and 3D printing technics had been used in recent years which simplified the surgical procedure and promoted success and accuracy. To assess the accuracy and outcome of VSP surgery, here we report our experience in maxillary reconstruction retrospectively. Method: Patients who received maxillary defect reconstruction from 2013 to 2020 were analyzed retrospectively. These patients were divided into 2 groups. Group 1 received VSP and 3D printed guiding plates in the surgery, while group 2 underwent free-hand surgery (FHS). Patients with different vertical and horizontal defects were classified according to Brown and Shaw classification. Clinical information and postoperative complications of all patients were collected. For patients with unilateral maxillary defect, orbit volume, orbit height and the contour of the reconstructed side were compared with the normal side. Result: 34 patients who achieved the criteria were analyzed, of which 20 patients underwent VSP surgery. There were primary and secondary reconstruction cases in both two groups. Vascularized iliac crest flap was used in 3 cases and fibula flap was performed in the other cases. One flap collapse occurred in FHS group. Seven patients in VSP group received dental implants, while the number in FHS group was 0. In vertical class Ⅲ cases, the differences in orbit height (ΔD) and orbit volume (ΔV) between normal side and reconstructed side were measured and compared in the two groups. The mean ΔD is 1.78±1.33mm in VSP group and 4.25±0.95mm in FHS group, while the mean ΔV is 2.04±0.85cm3 in VSP group and 3.25±0.17cm3 in FHS group. The alterations of orbit height and volume in VSP group were much smaller than that in FHS group with statistical significance. From the perspective of aesthetics, the color-gradient map indicates a more symmetric and smoother curve of post-operation appearance in VSP group. Conclusion: Compared with traditional free-hand surgical technics, VSP and 3D printing guiding plates can allow for a more accurate maxillary reconstruction with improved aesthetics and functions.